O espaço-tempo da educação infantil e a relação com a natureza - Lemes, Mariana Borges (2024)
This dissertation is located in the research line: Public policies, educational practices and their interfaces, the Graduate Program in Education of the Federal University of Santa Maria. Integrates the research: Childhoods, Cultures and Educational Practices in Early Childhood Education Contexts, coordinated by Professor Dr. Sueli Salva. It is established as a research problem: what are the possibilities of experiences with the external environment experienced by children in a public kindergarten school in the city of Santa Maria/RS? As a general objective, it was stressed to understand, from educational practices carried out in a in which times and spaces children experience experiences of contact with nature that can configure as a process of biophilia and disentanglement of childhood. As specific objectives, it was intended: to understand whether there are changes in the modes of interaction between children in different spaces of the school; to monitor the experiences of children in the external spaces of the Municipal School of Early Childhood Education and the modes of interaction with the environments. It is justified, considering the numerous questions related to the nature deficit (LOUV, 2016) and the pairing of childhoods, which children of early childhood education are submitted daily. It began with an exploratory period of the research, carried out in two public Early Childhood Education schools of Santa Maria/ RS and was elected one of them, considering the need for a long time proximity to it. The methodology is a qualitative approach, ethnographic in the area of education with children, and the information was produced from observations of the experiences of children, from two classes of preschool that were recorded in a field diary. The theoretical framework is organized based on Edward Wilson (1984, 2002), Léa Tiriba (2005, 2010, 2018), Richard Louv (2016), Manuel Sarmento (2002, 2003, 2008 and 2013), William Corsaro (2009, 2011), Ana Lúcia Goulart de Faria and Daniela Finco (2011), Ailton Krenak (2022), among others. The analysis of the information produced in this research occurred in a descriptive and interpretative way in the light of the references of this work. At the end, it is understood that, in this school, there was a movement to unpair children as a way to educate them for life.